The Neural Correlates of Access Consciousness and Phenomenal Consciousness Seem to Coincide and Would Correspond to a Memory Center, an Activation Center and Eight Parallel Convergence Centers - Frigato, Giancarlo (Frontiers in Psychology, 2021)
An increasing number of authors suggest that the neural correlates of consciousness have no selective, executive, or metacognitive function. It is believed that attention unconsciously selects the contents that will become conscious. Consciousness would have only the fundamental function of transforming the selected contents into a format easily used by high-level processors such as working memory, language, or autobiographical memory. According to Dehaene, the neural correlates of access consciousness (cognitive consciousness) constitute a widespread network in the frontal, parietal and temporal cortices. While Tononi localized the correlates of phenomenal consciousness (subjective consciousness) to a posterior "hot zone" in the temporo-parietal cortex. A careful examination of the works of these two groups leads to the conclusion that the correlates of access and phenomenal consciousness coincide. The two consciousnesses are therefore two faces of the same consciousness. A review of the literature of the pathology called “neglect” confirms this. Two of the ten correlates of consciousness are 1) the seat of memory and 2) the activation of the remaining eight correlates; these would act simultaneously in parallel and in close connection. From study of the “imagery” it can be deduced that each of these eight correlates would operate as a center of convergence in the third person linking the sensory-motor-emotional areas and the corresponding memories. This mechanism would produce a single consciousness with both its cognitive and subjective contents, all connected to the "body". The first four centers of convergence appear in the most evolved fish and gradually reach eight in humans.